Characteristics and treatment results of patients with gastroenteropancreatic neuroendocrine tumors in a tertiary care centre - Shouki Bazarbashi; Mohamed Aseafan; Tasnim Elgazzar; Maha Alkhayat; Abdulrahman Alghabban; Marwa I. Abdelgawad; Bader Alshamsan; Aisha Alshibany; Tusneem Elhassan; Ali Aljubran; Ahmed Alzahrani; Hindi Alhindi; et al. (BMC Endocrine Disorders, 2023)
Abstract Background Gastroenteropancreatic Neuroendocrine tumors (GEP-NET) are rare neoplasms with limited reported data from the Middle East. Our study aims to report the clinicopathological feature, treatment patterns, and survival outcomes of patients with GEP-NET from our part of the world. Methods Medical records of patients diagnosed with GEP-NET between January 2011 and December 2016 at a single center in Saudi Arabia were reviewed retrospectively, and complete clinicopathological and treatment data were collected. Patients’ survival was estimated by the Kaplan–Meier method. Results A total of 72 patients were identified with a median age of 51 years (range 27–82) and male-to-female ratio of (1.1). The most common tumor location was the pancreas (29.1%), followed by small bowel (25%), stomach (12.5%), rectum (8.3%), colon (8.3%), and appendix (6.9%). Forty-one patients (57%) had well-differentiated grade (G)1, 21 (29%) had G2, and 4 (6%) had G3. In five patients, the pathology was neuroendocrine carcinoma and in one it could not be classified. 54.2% of the patients were metastatic at diagnosis. Forty-two patients underwent surgical resection as primary management while 26 underwent systemic therapy, three patients were put on active surveillance, and one was treated endoscopically with polypectomy. The 5-year overall survival and progression-free survivals were 77.2% and 49%, respectively, for the whole group. Patients with G1 and 2 disease, lower Ki-67 index, and surgically treated as primary management had significantly better survival outcomes. Conclusion Our study suggests that the most common tumor locations are similar to western reported data. However, there seems to be a higher incidence of metastatic disease at presentation than in the rest of the world.